Analisis Antioksidan Ekstrak Etil Asetat Kulit Buah Manggis (Garcinia mangostana L.) Dengan Metode Dpph (1,1difenil-2-pikrilhidrazil) - Dewi Sartika; St Chadijah; Iin Novianty (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
Mangosteen fruit (Garcinia mangostana L.) is a potential source of natural antioxidant. This research can be seen through comparison of the effect of the solvent ethyl acetate for extract mangosteen rind (garcinia mangostana L.) the optimal antioxidant substances for withdrawal. Method used is maceration extraction using methanol and liquid phase using three variable 1:3, 1:4 and 1:5. The test Includes a qualitative and quantitative test of antioxidant. The results of the qualitative test show the presence of antioxidant in the yellow extract of mangosteen rind which turn purple discoloration on color test and the emergence of patches of yellow with purple backgroud on TLC when sprayed solution of DPPH 40 ppm. Then quatitativ test retrieved % high curbs in comparison 1:3.